Ameliorative Effects of Humulus japonicus Extract and Polysaccharide-Rich Extract of Phragmites rhizoma in Rats with Gastrointestinal Dysfunctions Induced by Water Avoidance Stress. (21st January 2022) - Thein, Wynn; Choi, Won Seok; Po, Wah Wah; Khing, Tin Myo; Jeong, Ji Hoon; Sohn, Uy Dong
Abstract : Chronic stress can cause the gastrointestinal disorders characterized by an altered bowel movement and abdominal pain. Studies have shown that Humulus japonicus extract (HJE) has anti-inflammatory and antidiarrheal effects, and Phragmites rhizoma extract (PEP) has antioxidative and antistress effects. The present study aimed to investigate the possible effects of HJE and PEP in rat models with stress-induced gastrointestinal dysfunctions. The rats were exposed to water avoidance stress (WAS, 1 h/day) for 10 days to induce gastrointestinal disorders. We found that WAS significantly increased fecal pellet output during 1 h stress, gastric emptying, colonic contractility, and permeability compared to the normal rats. Pretreatment with HJE and PEP (0.25 and 0.5 mL/kg, both administered separately) improved the increased gastric emptying and colonic contractility induced by electrical field stimulation, acetylcholine, and serotonin and also alleviated the increased colonic permeability. HJE and PEP also increased the claudin-1 and occludin expressions, reduced by WAS. WAS increased the concentration of TNF- α and TBARS and reduced FRAP. HJE and PEP recovered these effects. HJE and PEP improved the gastrointestinal disorders induced by WAS by upregulating the tight junction protein, possibly acting on cholinergic and serotonergic receptors to abolish the colonic hypercontractility and hyperpermeability and degradation of inflammatory cytokines via an antioxidant effect.